Exploring Relationship between Online Connectedness and Employee Perception of Supervisor Openness - Onobhayedo, Pius A. (Archives of Business Research, 2018)
As online connectedness continues to be a global phenomenon, this paper presents an examination of relationship between online connectedness of superior and subordinate, and the perceived openness of supervisors by employees. Using questionnaire as instrument, survey was carried out among employees in two countries (Nigeria and Spain) with disparate levels of infrastructure maturity as a way of facilitating generalizability of findings. Results show that the two connectedness scenarios studied were positively related to the perceived openness of managers by employees. It could be inferred from these findings that openness towards employees exhibited by supervisors online could enhance the level of positive communication climate in organizations as the latter has been suggested to be influenced by the perceived openness of the immediate supervisor.